Solid lipid nanoparticles of irbesartan: preparation, characterization, optimization and pharmacokinetic studies (Brazilian Journal of Pharmaceutical Sciences, 2017)
Irbesartan is an antihypertensive with limited bioavailability and solid lipid nanoparticles (SLN) is one of the approaches to improve bioavailability. Solid lipid nanoparticles were prepared using glyceryl monostearate by solvent emulsification method followed by probe sonication. Irbesartan loaded SLNs were characterized and optimized by parameters like particle size, zeta potential, surface morphology entrapment efficiency and in vitro release. The optimized formulation was then further evaluated for the pharmacokinetic studies in Wistar rats. Irbesartan-loaded SLN of particle size 523.7 nm and 73.8% entrapment efficiency showed good bioavailability in Wistar rats and also showed optimum stability in the studies. The SLN prepared using glyceryl monostearate by solvent emulsification method leads to improve bioavailability of the drug.